Performance evaluation of wireless sensor network MAC protocols with early sleep problem. (3rd May 2020) - Soni, Gulshan; Selvaradjou, Kandasamy
Energy efficiency and increased throughput are the two major goals in the design of MAC protocols in wireless sensor networks (WSNs). The traditional sensor-MAC (S-MAC) and timeout-MAC (T-MAC) protocols have been proposed to achieve these dual desirable goals by proper scheduling of duty cycles. Although these protocols have been proved to excel the performance when compared with their predecessor protocols for MANETs, the idea of duty cycling, if not tuned carefully may not work well in some linear chain topologies. We, in this paper investigated the 'early sleep' problem in specific topologies which results in undesirable extended latency in packets delivery. In this paper, we evaluated the performance of T-MAC protocol with early sleep problem. As a solution to this problem, this work also proposes a disable extended timeout MAC (DETMAC) protocol that helps the forwarding nodes towards the sink node to adaptively re-schedule their sleep/wakeup timing. It is shown through simulation results that our proposed DETMAC protocol outperforms in the terms of throughput and energy efficiency when compared to T-MAC and its variants.